Gymkhana and pylon slalom driving training effects on the cerebellum structure. (20th November 2021) - Shimizu, Toshiyuki; Gheorghe, Lucian A.; Nemoto, Kiyotaka; Horie, Tomohiko; Takano, Susumu; Haida, Munetaka
Highlights: Advanced driving training was conducted on a Gymkhana and a pylon slalom courses. Change of brain structure before and after training was investigated by voxel-based morphometry method. Increasing the volume of right side cerebellum after training were observed. Abstract: To develop a suitable automobile design as per each driver's characteristics and state, it is important to understand the brain function in acquiring driving skills. Reportedly, the brain structures of professionals, such as athletes and musicians, and those who have received training in special skills, undergo changes with training. However, the development process of the brain in terms of acquiring driving skills has not yet been clarified. In this study, we evaluated the effects of driving training on the brain and observed an increase in the volume of the right cerebellum after short-term training (3 days). The right cerebellum is responsible for controlling the right hand and right foot, which are important for driving. Drivers train to control a vehicle smoothly at high speeds at gymkhana and pylon slalom courses, which are often used in motor sports. The brain structure was analyzed before and after training using magnetic resonance imaging. Voxel-based morphometry was used to assess possible structural changes. First, the lap times after training were clearly shortened and vehicle dynamics were more stable, indicating that the drivers' skill level clearly improved. Second, brain structural analysis revealed a volumetric increase in the right cerebellum. The cerebellum is involved in the process of learning sensory motor skills, such as smooth steering and pedal operations, driving course shape, and vehicle size perception. These results suggest a new inner model for driving operation and support the hypothesis that motor learning affects the cerebellum during vehicle driving training.